Reflective enquiry into therapeutic institutions - Day, Lesley; Pringle, Pam; Bell, David (Psychoanalyst); Healy, Kevin (Cassel Hospital monograph series, 2001)
Therapeutic practice needs constant examination to ensure that it remains responsive and dynamic. Living organisms must communicate with their environment if they are to survive, and institutions are no different. This monograph, the second of the Cassell Hospital series, explores this concept further. By reading it, ideas and thinking will be sparked off that will help other organisations promote their own culture of enquiry.